Experimental study on an IC engine in-cylinder flow using different steady-state flow benches - M. El-Adawy; M.R. Heikal; A. Rashid A. Aziz; M.I. Siddiqui; Hasanain A. Abdul Wahhab (Alexandria Engineering Journal, 2017)
In-cylinder air flow structures are known to strongly impact on the performance and combustion of internal combustion engines (ICE). Therefore the aim of this paper is to experimentally study an IC engine in-cylinder flow under steady-state conditions. Different methods can be used to characterize the in-cylinder flow which are optical engines and laser diagnostics, computational fluid dynamic and steady-state flow bench. Here we are concentrating on two different types of flow benches. The first (Ricardo) uses the impulse torque meter method while the other (FEV) uses the paddle wheel technique. The experiments were carried out on the same cylinder head and the same pressure difference across the inlet valves of 600 mmH2O in order to compare the results. The experimental results are presented in terms of the measured air flow rate, flow coefficient, discharge coefficient and non-dimensional rig tumble. Moreover, number of modifications were conducted on the FEV flow bench in order to apply particle image velocimetry measurements on the vertical tumble plane, which passing through the middle of the cylinder at different valve lifts. The results show that a reasonably good level of agreement can be achieved between both methods, providing the methods of calculations of the various parameters are consistent. Keywords: In-cylinder flow, Flow bench, Tumble motion, Flow coefficient, Particle image velocimetry